PERSONALITY ANALYSIS PROFILE TRAINER WITH DISC METHOD AS A DETERMINANT OF PSYCHOLOGICAL TEST FOR SELECTION OF CANDIDATES FOR TRAINERS AT AL AZHAR - DEPOK MAS - Khairunnisa Khairunnisa; Dewi Ulfah Arini; Franka Hendra (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
The need for social workers in the regions of Eastern Indonesia, especially in the fields of human enrichment and the development of the Islamic religion, makes it necessary to have prospective workers. Da'i as a trainer at the Al Azhar Zakat Charity Institute. Therefore, it is necessary to select candidates for Da'i according to the characteristics of the demands as a trainer. Selection using the DISC method already has high validity and its effectiveness has been used in several aspects and fields of work to measure individual aspects of Mental Readiness and Cognitive. DISC was created to help individuals explore their personality and behavior types so that they can better understand themselves and others (Bonnstetter & Suiter, 2011: 32). The method with a comparative research design is used to determine the profile of Dai as a trainer by using psychological tests and DISC analysis. The combination of DISC results is known that the prospective Da'i participants have a dominant combination of CS/DI, SC/DI, SC/ID, where this type tends to obey the rules and be consistent. In conclusion, Candidates for preachers on average have the ability to influence as a form of da'wah business that is inherent in them.